Sharia Economic Law Perspective on The Concept of Halal Haram on Food at SUSHI HIRO - Ivana, Rossalind Mutiara; Muthoifin, Muthoifin (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to examine the application of the concepts of halal and haram as an ethical foundation in the practice of selling food in Sushi Hiro restaurants that do not have official halal certification, reviewed from the perspective of sharia economic law. The theoretical framework of this research is based on the concepts of halal and haram in Islamic fiqh, the principles of sharia economic law, and maqasid al-sharia, especially the protection of religion (hifz al-din), soul (hifz al-nafs), and property (hifz al-mal). The framework is used to assess the ethical responsibility of business actors as well as legal certainty in modern culinary business practices. The literature review refers to previous research on halal certification and the protection of Muslim consumers, especially generation Z. The literature shows that halal certification plays an important role in building Muslim consumer trust, although generation Z's consumption decisions are often influenced by lifestyle and social trends. Studies on non-halal certified Japanese restaurants from the perspective of sharia economic law are still relatively limited. The research methodology uses a normative-descriptive qualitative approach with case studies. The type of research is in the form of library research that utilizes secondary data, such as laws and regulations, fiqh muamalah literature, sharia economic law books, and relevant journal articles. Data analysis was carried out in a descriptive-analytical manner by linking legal norms and sharia principles to the practice of selling food at Sushi Hiro. The results of the study show that the absence of halal certification puts Sushi Hiro products in the category of syubhat and has the potential to contain gharar elements due to the unclear ingredients and production process. In addition, the consumption of Generation Z Muslims is more influenced by trends than by halal certainty. These findings affirm the importance of transparency, ethical responsibility of business actors, and halal certification as an instrument of consumer protection and increasing public trust.